Empowering of women in contemporary Uganda : real or symbolic / R osalind Boyd. - Boyd, Rosalind (Quebec city, Canada : Laval University, 1989)
This was a paper originally presented at the 12th annual conference of the Canadian research institute for the advancement of women and dev elopment.
AR/SIC/1/2/19
English
Shelf no. 2